Implementasi Pendidikan Karakter dalam Pembelajaran IPS di Sekolah Dasar - Agata, Febriella Happy; Lasmawan, Wayan; Kertih, Wayan (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2024)
Social Studies (IPS) lessons explore various aspects of life, including education. The purpose of learning IPS is to enhance students' capacity so that they possess good character in school, family, society, and the nation. This study employs a descriptive qualitative research approach. To collect data in this research, the researcher used field observations, interviews with informants, and document analysis. The research results indicate that teachers utilize various programs to assist in the development of students' character. Collaboration between teachers and parents is one example.